Health-improving training of preschoolers' with respiratory diseases parents as an integral part of rehabilitation programs. - Areshina Ju.B (Kharkov National Pedagogical University, 2011)
The necessity of health-improving training of preschoolers' with respiratory diseases parents is reasoned. The reasoning is held theoretically and practically. The list of lecture topics for this contingent of parents is created. It contains plans of lectures, designed for covers a hospital and a post- hospital periods of physical rehabilitation. In experiment took part 42 families of children aged 4-6 years old.